High-voltage FinFET with floating poly and high-k material for enhanced intrinsic gain and safe operating area - Kyounghwan Oh; Hyangwoo Kim; Yijoon Kim; Hyeongseok Yoo; Minkeun Choi; Wooyeol Maeng; Sutae Kim; Hyung-Jin Lee; Chang-Ki Baek (Scientific Reports)
Abstract We propose a new drain-extended FinFET (DeFinFET) that can improve the intrinsic gain (g m/g ds) and the electrical safe operating area (SOA). This structure features a novel utilization of the drain potential by using a floating poly (FP) and split high-k material (HK) on the drain and drift regions. This method effectively controls the potential drop profile within the drift region, which makes a uniform electric field distribution in the gate-on state. The evenly distributed electric field significantly increases the on-state breakdown voltage (7.33 V) compared to a conventional structure (5.89 V). In addition, it prevents the device from operating in an undesirable quasi-saturation mode, even after space charge modulation. This operation distinguishes our results from other studies, showing a notable improvement in g m/g ds. Moreover, electron accumulation is induced in the drift region, leading to a significant decrease in the on-resistance. As a result, the proposed device demonstrates clear advantages in high-voltage applications with a 45% expanded electrical SOA over conventional DeFinFET.